2018
DOI: 10.1590/2317-1782/20182017013
|View full text |Cite
|
Sign up to set email alerts
|

Pseudopalavras para terapia fonológica validadas por juizes especialistas

Abstract: RESUMO Objetivo Criar uma lista de pseudopalavras baseada em ambientes favorecedores e submeter esta ao julgamento de juízes especialistas, a fim de se obter uma lista validada de pseudopalavras que possam ser utilizadas em terapia. Método Buscou-se um estudo que analisou os ambientes favorecedores de todos os fonemas do Português Brasileiro e, a partir de seus dados, criou-se uma lista de pseudopalavras para cada fonema, em diferentes níveis de favorecimento. A amostra julgadora da lista foi composta por … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The expert judges were asked to determine whether the stimuli were representative and consistent with the goals of the instrument (Mohajan, 2017;Zamanzadeh et al, 2015). The CVR was used to measure inter-rater agreement and determine the extent to which an item was considered essential for the test, as has been done in previous studies (Al-Thalaya et al, 2017;Keske-Soares, 2018). Previous instrument adaptation studies which used Gwet's firstorder agreement coefficient (AC1) found that values over 0.70, such as those obtained in the present study, are indicative of satisfactory agreement between raters (Bukenya et al, 2017;Erivan et al, 2019).…”
Section: Nonverbal Praxismentioning
confidence: 99%
“…The expert judges were asked to determine whether the stimuli were representative and consistent with the goals of the instrument (Mohajan, 2017;Zamanzadeh et al, 2015). The CVR was used to measure inter-rater agreement and determine the extent to which an item was considered essential for the test, as has been done in previous studies (Al-Thalaya et al, 2017;Keske-Soares, 2018). Previous instrument adaptation studies which used Gwet's firstorder agreement coefficient (AC1) found that values over 0.70, such as those obtained in the present study, are indicative of satisfactory agreement between raters (Bukenya et al, 2017;Erivan et al, 2019).…”
Section: Nonverbal Praxismentioning
confidence: 99%